Synthesis and Lithium Storage Properties of Zn, Co and Mg doped SnO2 Nano Materials. (1st September 2017) - Nithyadharseni, P.; Abhilash, K.P.; Petnikota, Shaikshavali; Anilkumar, M.R.; Jose, Rajan; Ozoemena, K.I.; Vijayaraghavan, R.; Kulkarni, Pranav; Balakrishna, Geetha; Chowdari, B.V.R.; Adams, Stefan; Reddy, M.V.
Graphical abstract: Highlights: First time, we synthesized and studied the electrochemical properties of Sol-gel Mg and Co doped SnO2 . Small particle size of 5.5 nm was observed for Co −SnO2 than < 10 nm for Zn and Mg −SnO2 . Exhibited specific capacity of 573 mAh g −1 (83% capacity retention) for Co −SnO2 at 60 mA g −1 . At 1000 mA g −1, high specific capacity of 415 mAh g −1 was obtained for Co-SnO2 . Abstract: In this paper, we show that magnesium and cobalt doped SnO2 (Mg-SnO2 and Co-SnO2 ) nanostructures have profound influence on the discharge capacity and coulombic efficiency of lithium ion batteries (LIBs) employing pure SnO2 and zinc doped SnO2 (Zn-SnO2 ) as benchmark materials. The materials were synthesized via sol-gel technique. The structural, chemical and morphological characterization indicates that the Zn, Mg and Co dopants were effectively implanted into the SnO2 lattice and that Co doping significantly reduced the grain growth. The electrochemical performances of the nanoparticles were investigated using galvanostatic cycling, cyclic voltammetry and electrochemical impedance spectroscopy (EIS). The Co-SnO2 electrode delivered a reversible capacity of around 575 mAh g −1 at the 50th cycle with capacity retention of ∼83% at 60 mA g −1 current rate. A capacity of ∼415 mAh g −1 when cycling at 10 3  mA g −1 and >60% improvement in coulombic efficiency compared to the pure compound clearly demonstrate the superiority of Co-SnO2 electrodes. The improved electrochemical properties are attributed to the reduction in particle size of the material up to a few nanometers, which efficiently reduced the distance of lithium diffusion pathway and reduction in the volume change by alleviating the structural strain caused during the Li + intake/outtake process. The EIS analyses of the electrodes corroborated the difference in electrochemical performances of the electrodes: the Co-SnO2 electrode showed the lowest resistance at different voltages during cycling among other electrodes.